THE EVOLUTION OF BANKING SECTOR REGULATION IN SUPPORTING INDONESIA'S NATIONAL ECONOMIC DYNAMICS: A LITERATURE REVIEW OF MONETARY POLICY, MACROPRUDENTIAL SUPERVISION, AND POST-FINANCIAL REFORM REGULATORY HARMONISATION FOR OPTIMISING CONTRIBUTIONS TO DEVELOPMENT - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
Regulatory harmonisation in the financial sector is key to ensuring economic stability while maximising the contribution of the banking sector to national development in Indonesia. Harmonious regulations not only help prevent instability, but also support innovation and efficiency in financial services. Thus, financial institutions can focus more on developing products and services that accelerate financial inclusion in society and support small and medium-sized enterprises, which are the main pillars of the economy. Digitalisation and technological innovation, including collaboration with fintech, are important elements in supporting the competitiveness and sustainability of the financial sector. Digital transformation enables banks to offer more inclusive and personalised financial solutions tailored to the specific needs of customers. In addition, adaptive regulations are needed to balance good risk management with the need for innovation, thereby creating a dynamic financial ecosystem that supports broader economic growth.